Development of Animated Video Based on the ADDIE Model as Anticipatory Guidance for KIPI Covid-19 Vaccination at SMAN 2 Bangkalan - Eka Suci Daniyanti; M Lutfi; Nailufar Firdaus (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
ABSTRACT This study aimed to produce animated videos of behavior life clean and healthy (PHBS) as anticipatory guidance or guide prevention incident following post-immunization (KIPI) Covid-19 in high school students. This study used design study Research and Development with a developed concept namely the ADDIE model. The ADDIE development model includes 5 stages that are Analyze (analysis), Design (design), Develop (development), Implement (implementation), and Evaluate (assessment). The trial used is one group pre-test – post-test design with a sample of as many as 253 students. Data collection using a questionnaire with as many as 10 questions filled out by respondents before (pre-test) and after (post-test) using video animation. Research results in results obtained a significance value of 0.000 <α 0.05. This means that animated videos on clean and healthy living behaviors are very effective as a means of anticipatory guidance information or prevention of post-immunization adverse events (KIPI) for the Covid-19 vaccine.